Decreasing land use and increasing information infrastructure: Big data analytics driven integrated online learning framework in rural education - Wei, Na (Frontiers in Environmental Science, 2022)
Nowadays, Big Data Analytics (BDA) attracted considerable interest due to its tremendous social and scientific value. The use of traditional rural education land is being replaced by the emerging network classroom. With the fast-growing data and information numbers at present, the IT world’s educational system are changing rapidly. The performance of rural school students is less satisfactory, and many rural schools have disadvantageous of having distanced from a nearby university. The schools in the countryside are located in the remote land. Rural schools are smaller and costlier to operate and likely to have a teacher shortage. These problems are all expected to be solved by the application of big data. In this paper, Big Data Analytics driven Integrated Online Learning Framework (BDAIOLF) has been proposed for rural education. The study showed that the conditions, social impact, performance, and effort expectations facilitating behavioral intentions have been essential determinants for the use of ICT for educational purposes. Data have been collected through a literature study, interviews between individuals and focus groups. Key findings indicated that rural school success is influenced by a number of factors relating to the core values of education, the teacher-learner relationship, the proficiency of English, and parental participation in teaching and learning. In rural schools, however, teaching and learning are influenced by factors such as topics, the work environment, genetic characteristics, and environmental conditions. The construction of information infrastructure is an important reason for the reduction of rural education land.